Artificial nose for alcohol detection - Mohamad Koya, Muhamad Aslam; Mohamad Ibrahim , Azhar; Akmeliawati, Rini; Sutjipto, Agus Geter Edy; Faris, Waleed Fekry (2010)
Our research presents the development of an artificial olfactory system as a non-destructive instrument to detect and measure concentration of alcohol. The hand-held unit will consist of an alcohol sensor, a microcontroller to calculate the concentration of alcohol and blood alcohol concentration (BAC), and an LCD display, which will display the percentage of alcohol concentration detected.